Educational Needs of Midwifery Students regarding Mother and Infant Mortality Prevention Services in Critical Situations - Ziba Taghizadeh; Ali Montazeri; Mahsa Khoshnamrad (Tehran University of Medical Sciences, 2015)
Background & Aim: Midwives are responsible for providing health services to mothers and infants in crises. The aim of this study was to identify educational needs of midwifery students regarding mother and infant mortality prevention in crisis situations .   Methods & Materials: In this cross-sectional study, all 235 final-year BSc. and MSc. midwifery students were selected from four medical universities located in Tehran. Informed consent forms were completed and signed by the students. The students completed a researcher-made two-section questionnaire including demographic items and educational needs items regarding mother and child preventive services in crises. Data were analyzed in the SPSS .    Results: Mean score of the m aternal and neonatal prevention service dimensions were 70±21.5 ( out of 105 ) and 46.7 ± 9 (out of a 65), respectively. Most of the students (86.8% ) declared that their academic education did not prepare them for their roles in crises. Only 10.6% of the students had some courses on crisis and 11.5% of them had the experience of dealing with crisis. The students in the BSc. degree had more educational needs in both dimensions compared to the students in the MSc. degree (P<0.046). There were significant relationships between the age of students (P<0.001), their clinical experience (P<0.001), previous educational courses (P<0.001) and experience in crisis (P<0.05) with the educational needs. There was no significant relationship between the educational needs and the students’ universities ( P>0.05 ) .   Conclusion: Educational curriculums should be revised regarding actions to be done on prevention of mother and infant mortality in crises .